2022
DOI: 10.37745/ijelt.13/vol10n51229
|View full text |Cite
|
Sign up to set email alerts
|

The State of Reading in Tertiary Institutions: A Pragmatic Analysis of a Ghanaian University

Abstract: Positive attitude towards learning, ability to independently think and work, ability to inquire, good command over English language are often considered characteristics of a tertiary education student. To excel, the student must be able to read and make meaning out of what is read as reading underlies all forms of academic study and is crucial to academic success (Grabe, 2009). This study investigated the state of reading among tertiary education students. The sequential explanatory mixed method design was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, the researcher designed supplementary materials to support the students about learning writing, especially procedure text, in a form of PowerPoint that was in line with the students' needs. This presentation is regarded as a useful educational tool and a vital component of improving efficient teaching and learning due to the fact that PowerPoint allows users to include both audio and visual components in presentations (Agbevivi, 2018). The supplementary materials were designed based on the task-based framework by Willis, 1996 as the teacher suggested in the interview.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researcher designed supplementary materials to support the students about learning writing, especially procedure text, in a form of PowerPoint that was in line with the students' needs. This presentation is regarded as a useful educational tool and a vital component of improving efficient teaching and learning due to the fact that PowerPoint allows users to include both audio and visual components in presentations (Agbevivi, 2018). The supplementary materials were designed based on the task-based framework by Willis, 1996 as the teacher suggested in the interview.…”
Section: Discussionmentioning
confidence: 99%
“…It was further confirmed that 96 (97.4%) students mentioned that prereading activities activate their background knowledge about the topic of the text and as such helps them in learning more. This finding implies that pre-reading activities have positive effects on pupils' performance in reading comprehension (Asgar, 2016) and as a matter of fact, the more they read, the more they learn (Agbevivi, 2022). Pre-reading activities are thus, invaluable tools in reading comprehension classrooms.…”
Section: Pupils' Perspectives On the Impact Of Pre-reading Activities...mentioning
confidence: 97%
“…Reading can entertain and amuse the reader, but most of all it enriches the reader with knowledge and experiences narrated. Agbevivi (2022) projects reading as the most vital skill for students; consequently, it is believed that the more one reads, the more one learns. Reading purely for leisure is fun but when reading skills and strategies are perfected at an early stage, it produces better and more comprehensive readers with purpose.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case a computer with multimedia support can present a display in the form of text that is not monotonous and is more interesting and more interactive. This display will make users more free to choose, filter, and understand the knowledge they want to know (Agbevivi, 2018;Osman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%